Size Perception Biases Are Temporally Stable and Vary Consistently Between Visual Field Meridians. (September 2019) - Schwarzkopf, Dietrich S.
The apparent size of visual stimuli depends on where in the visual field they appear. We recently presented a model of how size perception could be biased by stimulus encoding in retinotopic cortex. However, it remains unclear if such perceptual biases are instead trivially related to discrimination ability and if they are temporally stable. An independent test of the model is also still outstanding. Here, I show that perceptual biases are stable across stimulus durations between 50 and 1, 000 milliseconds, even though discrimination ability unsurprisingly improves with duration. Furthermore, perceptual biases are stronger along the vertical than the horizontal meridian, which mirrors reported differences in spatial vision and the positional selectivity of early visual cortex. Taken together, these findings support our model of how size is inferred from cortical responses.